The Johansson‐Molloy theorem for DP‐coloring - Bernshteyn, Anton (Random structures & algorithms, 2019)
The aim of this note is twofold. On the one hand, we present a streamlined version of Molloy's new proof of the bound χ(G)≤(1+o(1))Δ(G)/lnΔ(G) for triangle‐free graphs G, avoiding the technicalities of the entropy compression method and only using the usual “lopsided” Lovász Local Lemma (albeit in a somewhat unusual setting). On the other hand, we extend Molloy's result to DP‐coloring (also known as correspondence coloring), a generalization of list coloring introduced recently by Dvořák and Postle.